Activation of the Nrf2 Pathway by Inorganic Arsenic in Human Hepatocytes and the Role of Transcriptional Repressor Bach1. (7th May 2013) - Liu, Dan; Duan, Xiaoxu; Dong, Dandan; Bai, Caijun; Li, Xin; Sun, Guifan; Li, Bing
Abstract : Previous studies have proved that the environmental toxicant, inorganic arsenic, activates nuclear factor erythroid 2-related factor 2 (Nrf2) pathway in many different cell types. This study tried to explore the hepatic Nrf2 pathway upon arsenic treatment comprehensively, since liver is one of the major target organs of arsenical toxicity. Our results showed that inorganic arsenic significantly induced Nrf2 protein and mRNA expression in Chang human hepatocytes. We also observed a dose-dependent increase of antioxidant response element- (ARE-) luciferase activity. Both the mRNA and protein levels of NAD(P)H:quinone oxidoreductase 1 (NQO1) and heme oxygenase-1 (HO-1) were all upregulated dramatically. On the other hand, entry and accumulation of Nrf2 protein in the nucleus, while exportting the transcriptional repressor BTB and CNC homology 1 (Bach1) from nucleus to cytoplasm, were also confirmed by western blot and immunofluorescence assay. Our results therefore confirmed the arsenic-induced Nrf2 pathway activation in hepatocytes and also suggested that the translocation of Bach1 was associated with the regulation of Nrf2 pathway by arsenic. Hepatic Nrf2 pathway plays indispensable roles for cellular defenses against arsenic hepatotoxicity, and the interplay of Bach1 and Nrf2 may be helpful to understand the self-defensive responses and the diverse biological effects of arsenicals.